SISTEM INFORMASI OBYEK WISATA GERBANG MAS BAHARI WATERPARK TEGAL BERBASIS WEB (Information Technology and Telematics, 2013)
The development of the world tourist attraction in Indonesia became one of the leading sources of foreign exchange earnings and substantial. Sights WaterPark Tegal is an object or a vehicle that consists of a variety of water games that is located in the town of Tegal. Although familiar with the interesting but quite less power because the object is still using the brochures and radio ads introducing the attractions. In addition it should still purchase tickets at counters WaterPark. It is an obstacle for visitors to be able to purchase tickets for visitors to come first in the queue following the vehicle after purchase at the counter. Making information systems Sights Mas the Gerbang WaterPark Tegal presumably can be a tool that can be used by the community to be able to answer all the obstacles that have been presented above. This research method is built using the Prototype. While the system is built using a PHP programming and PhpMyAdmin As with databases. This research resulted in a system of web-based data processing applications that can make a reservation and purchase tickets. Expected to exist in its application can help management and employees in carrying out operations and it can also promote any events organized by the Gerbang Mas Waterpark. Keyword : Tourism, purchase tickets, Web, Application